2012
DOI: 10.2136/sssaj2011.0160
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Nutrient Concentrations Related to Soil Sources across a Range of Sites in the Northeastern United States

Abstract: All rights reserved. No part of this periodical may be reproduced or transmitted in any form or by any means, electronic or mechanical, including photocopying, recording, or any information storage and retrieval system, without permission in writing from the publisher. Permission for printing and for reprinting the material contained herein has been obtained by the publisher. Foliar Nutrient Concentrations Related to Soil Sources across a Range of Sites in the Northeastern United StatesForest, Range & Wildland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…The residue was extracted in 30% H 2 O 2 to determine organically bound P. That residue was extracted in 1 mol/L HNO 3 at 108C to dissolve apatite-bound P in contact with the solution. Apatite is the primary source of P from mineral weathering, and using our method a previous study showed estimates of soil apatite correlate with litterfall P in northern hardwood forests (Lucash et al 2012). Finally, the residue from the apatite digestion was further digested in concentrated HNO 3 at 1508C for 3 h to estimate the amount of apatite P armored in biotite and chlorite.…”
Section: Soil Nitrogen and Phosphorusmentioning
confidence: 76%
“…The residue was extracted in 30% H 2 O 2 to determine organically bound P. That residue was extracted in 1 mol/L HNO 3 at 108C to dissolve apatite-bound P in contact with the solution. Apatite is the primary source of P from mineral weathering, and using our method a previous study showed estimates of soil apatite correlate with litterfall P in northern hardwood forests (Lucash et al 2012). Finally, the residue from the apatite digestion was further digested in concentrated HNO 3 at 1508C for 3 h to estimate the amount of apatite P armored in biotite and chlorite.…”
Section: Soil Nitrogen and Phosphorusmentioning
confidence: 76%
“…, Lucash et al. ). Compositing allows greater sampling intensity for the same cost, giving a better estimate of the mean, but at the expense of characterizing the variability.…”
Section: Discussionmentioning
confidence: 99%
“…The cost of analyzing multiple samples can be reduced by compositing sequential samples. It is also common to composite samples from multiple traps before chemical analysis (Knoepp et al 2008, Lucash et al 2012. Compositing allows greater sampling intensity for the same cost, giving a better estimate of the mean, but at the expense of characterizing the variability.…”
Section: Recommendations For Litterfall Measurementsmentioning
confidence: 99%
“…Sugar maple (Acer saccharum Marsh) is arguably the most ecologically and economically important species in the northern hardwood forests of eastern North America. Ecologically, sugar maple provides nutrient-rich litter to forest soils (Long et al 2009, Lucash et al 2012, promotes N mineralization and reduces leaching of nitrate into groundwater (Lovett et al 2004), and shapes the diversity of plant and animal communities (Beier et al 2012a). Economically, the tree provides the raw materials for a profitable maple syrup industry, provides dura-ble hardwood for furniture and flooring, and offers aesthetically pleasing fall foliage (Millers et al 1989).…”
Section: Introductionmentioning
confidence: 99%